Post-treatment of municipal wastewater using microalgae and activated sludge synergy - James, Abraham Olamilekan (2023)
The problem of untreated and inadequately treated wastewater still persists globally. This has not only contributed to the increasing environmental pollution loads, but has also failed to harness the bioeconomy materials present in wastewater. While the science of microalgae-based treatment technology has shown to be efficient for treatment and recovery of potential resource, the majority of the studies were conducted under controlled conditions. Therefore, this present study evaluated the performance of native microalgae-activated sludge (MAS) growth for tertiary treatment of anaerobically digested wastewater from an upflow anaerobic sludge blanket (UASB) in an outdoor lab-scale photobioreactors (2 L). Seven different conditions with distinct inoculum proportions (Conditions: 1 to 3 is MAS; 4 to 6 is microalgae controls; 7 is without inoculum) were operated in batch mode reactor in triplicate for 5-days of hydraulic retention time (HRT) at 11.5:12.5 Photo-hours, to identify the best inoculum proportion for adopted in pilot flat panel photobioreactor. Condition 1 (0.10gL-1: microalgae and 0.20gL-1: activated-sludge), with lowest MAS proportion showed the best outcome with cell density productivity (2.03 x 107 cells.mL-1) along with biomass of 0.13 g TSS.L-1.d-1 and the total phosphorus uptake (85.07%), total nitrogen uptake (66.14%), logarithmic removal (Log-Re) of bacterial pathogens (water quality indicators), which showed Log-Re (3.3 for total coliforms (137E+02 CFU.100 mL-1) and 4.7 for Escherichia coli (0.00E+00 CFU.100 mL-1)). The best performing MAS (condition 1) was tested in a pilot flat panel photobioreactor, alongside a control, inoculated with the microalgae proportion of the MAS, and operated under 5-days and 3-days HRT. The performance of the system was determined by the efficiency of nutrient removal and recovery, biomass sedimentation and removal of Escherichia coli and Total Coliforms. Results showed that high HRT favoured the performance of MAS with respect to biomass growth, with significantly higher (p < 0.05) removal efficiency, 88.0, 79.0, 59.5% for total phosphorus (TDP), ammonium nitrogen (NH+4-N), chemical oxygen demand (CODfiltered), respectively at 5 days HRT. The average biomass productivity and growth rate for HRTs 5 days and 3 days are 59.41±12.31 mg TSS L-1 d-1, 0.08±0.01 d-1 and 25.56±11.09 mg TSS L-1 d-1, 0.03±0.01 d-1, respectively. The log-Re > 4.0 CFUmL-1 and > 3.5 CFUmL-1 were achieved for E. coli and total coliforms, respectively at both HRTs, and showed the potential for agricultural use for complying with the WHO recommended standard of 103 MPN.100mL-1. Overall, results showed a promising feasibility of outdoor microalgae-based treatment of wastewater cost effectively. However, self-settling efficiency was conversely low 33.0 and 14.0% for HRTs 5 days and 3 days, respectively, and suspiciously impacted by high pH (> 10.0) on bacterial population and the dominance of non-mucilage Cyanobium sp. (98%).